Revisiting External Validity: Concerns about Trolley Problems and Other Sacrificial Dilemmas in Moral Psychology. Issue 9 (September 2014) - Bauman, Christopher W.; McGraw, A. Peter; Bartels, Daniel M.; Warren, Caleb
Abstract Sacrificial dilemmas, especially trolley problems, have rapidly become the most recognizable scientific exemplars of moral situations; they are now a familiar part of the psychological literature and are featured prominently in textbooks and the popular press. We are concerned that studies of sacrificial dilemmas may lack experimental, mundane, and psychological realism and therefore suffer from low external validity. Our apprehensions stem from three observations about trolley problems and other similar sacrificial dilemmas: (i) they are amusing rather than sobering, (ii) they are unrealistic and unrepresentative of the moral situations people encounter in the real world, and (iii) they do not elicit the same psychological processes as other moral situations. We believe it would be prudent to use more externally valid stimuli when testing descriptive theories that aim to provide comprehensive accounts of moral judgment and behavior.